2018
DOI: 10.1002/jbm.a.36491
|View full text |Cite
|
Sign up to set email alerts
|

Preparing and immobilizing antimicrobial osteogenic growth peptide on titanium substrate surface

Abstract: The inherent bioinertness and potential bacterial infection risk are the two leading causes for Ti implant failure. To improve osseointegration and antibiosis, in this work, a novel antimicrobial osteogenic growth peptide was first synthesized by conjugating osteogenic growth peptide (OGP) and ciprofloxacin (CIP). Then, the synthetic antimicrobial peptide was immobilized onto Ti implant surface for chemoselective binding via the amide reaction. Thereafter, the capabilities of modified Ti implant on osseointegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In order to successfully install the implants, researchers make efforts to create bioactive coating materials on titanium surface using different techniques. 1 , 2 In these studies, favorable osteogenic, angiogenic and antibacterial capacities of coating materials have been widely explored. 3 , 4 However, many coating materials with excellent properties mentioned above could not achieve satisfactory results in the subsequent in vivo studies in terms of the regeneration of bones.…”
Section: Introductionmentioning
confidence: 99%
“…In order to successfully install the implants, researchers make efforts to create bioactive coating materials on titanium surface using different techniques. 1 , 2 In these studies, favorable osteogenic, angiogenic and antibacterial capacities of coating materials have been widely explored. 3 , 4 However, many coating materials with excellent properties mentioned above could not achieve satisfactory results in the subsequent in vivo studies in terms of the regeneration of bones.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the release of chlorhexidine could facilitate osseointegration by completely preventing the formation of bacterial biofilm on the implant surface [ 96 ]. In addition, the failure of osseointegration caused by bacterial infection could be prevented by direct grafting of antibiotic ciprofloxacin on Ti implants or by loading ciprofloxacin on CS/nanoHA/Ti [ 97 , 98 ]. In order to obtain more superior antibacterial implants, Park et al loaded silver nanoparticles, cephalothin, minocycline (Mino), and amoxicillin on mesoporous TiO 2 .…”
Section: Local Drug Delivery Systems With Ti-based Implantsmentioning
confidence: 99%
“…Induced in vitro mineralization [29] SiO 2 /MgO doped HA -plasma spraying -↑ In vivo osteogenesis and osteointegration [35] Chitosan/gelatin/HA -LBL assembly -↑ Adhesion, proliferation and osteogenic differentiation of MSCs ↑ Adhesion and mitigation of HUVECs ↑ In vivo osteogenesis and angiogenesis [151] TNT -electrochemical anodization CaP -biomimetic coating -↑ Early stage in vivo osteointegration and mineralization [23] Ti6Al4V HA -plasma spraying ↑ Surface roughness ↑ Adhesion and attachment of osteoblast ↓ Osteosarcoma ↑ In vivo osteointegration [16] HA -magnetron sputtering Homogeneous crystalline coating - [24] Si doped HA -dip coating VEGF -physical adsorption ↑ Proliferation of pre-osteoblasts and endothelial cells ↑ In vivo osteointegration and angiogenesis in osteoporotic model [30] Biphasic CaP nHA -hydrothermal deposition -↑ Viability and osteogenic differentiation of MSC PEG -electrodeposition RGD/LF1-11 -covalent immobilization ↑ Hydrophilicity ↑ Osteoblast adhesion and spreading ↓ Adhesion and viability of S. sanguinis and protein adsorption [132] GL13K (AMP) -covalent immobilization ↑ Hydrophilicity Slightly ↑ surface roughness ↓ Viability of P. gingivalis ↑ Fibroblast viability and attachment [110] Osteogenic growth peptide/ciprofloxacin -covalent immobilization ↑ Hydrophilicity → Surface roughness ↑ Osteoblast spreading and osteodifferentiation [111] NO releasing coating -silanization, diazeniumdiolate functionalization ↓ Hydrophilicity ↑ Surface roughness ↓ Adhesion and colonization of S. aureus and P. aeruginosa No cytotoxicity to osteoblasts [161] Ag/PDA -physical adsorption -↓ Growth and colonization of S. mutans and P. gingivalis [162] Ag NPs/GO -electroplating Microstructured ↓ Adhesion and viability of S. mutans and P. gingivalis ↑ Cytotoxicity with higher GO and Ag NPs [163] GL13K/TNT -physical adsorption/electrochemical anodization -↓ Growth of F. nucleatum and P. gingivalis ↑ Proliferation and no cytotoxicity to MC3T3-E1 cells [124] Ag NPs/ vancomycin/TNTs -plasma immersion ion implantation (PIII)/lyophilization/electrochemical anodization -↓ Adhesion of S. aureus No cytotoxicity to fibroblasts [123] Ag ↑: enhancement; ↓: hindered effect; →: comparable result.…”
Section: Controllable and Homogeneous Coatingmentioning
confidence: 99%
“…A dual functional AMP was synthesized by conjugating osteogenic growth peptide with ciprofloxacin, and covalently immobilized on titanium surface. [ 111 ] Such AMP modified titanium promoted proliferation, spreading and osteogenic differentiation of osteoblasts. The sustained release of this AMP for 7 days led to less adhered and viable bacteria.…”
Section: Strategies To Realize Bacteriostatic and Bactericidal Perfor...mentioning
confidence: 99%